The influence of orientation of blast loading on quadrangular plates. (October 2018) - Chung Kim Yuen, S.; Butler, A.; Bornstein, H.; Cholet, A.
Abstract: This paper presents the results of experiments and numerical simulations carried out to characterise and assess the effects of orientation of blast loading onto a quadrangular plate. The study was carried out in two distinct arrangements. In one configuration, the explosive was tilted at different angles (0° (use as baseline for comparison), 15°, 30° and 45°) with respect to the target plate to provide different impact angles of the shock wave front with respect to the plate. In the other configuration, the target plate was tilted at two different angles (15° and 45°) with respect to the explosive. The blast load was achieved by detonating a 38 mm cylindrical disc of explosive. The stand-off distance, defined as the distance between the plate and the centre of the nearest face of the explosive cylinder, was kept constant at 40 mm. The mass of explosive was varied between 8 and 28 g of PE4 to achieve different responses of the plate ranging from large inelastic deformation to tearing of the structure. For all the different loading scenarios, the target plate consisted of a 2 mm thick DOMEX steel quadrangular plates with an exposed area of 300 × 300 mm. Each loading scenario was quantified in terms of impulse imparted onto the target in the axial direction of a horizontal ballistic pendulum. The damage was evaluated in terms of maximum deflection/tearing of the target plate. Numerical simulations was carried out in ANSYS ® AUTODYN ® using a coupled Eulerian and Lagrangian solver approach to provide insights in the mechanism of the blast load in terms of load distribution on the target plate. Highlights: Response of quadrangular steel plates to oblique blast load. The effect of detonating explosives in different orientations with respect to the target plate. The influence of tilting the target plates with respect to the explosive charge. Comparison between tilt of explosives and orientations of target plate. Insights in the mechanism of the blast load in terms of load distribution on the target plate.